Preparation method and application of a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material
By performing transition metal doping and dopamine hydrochloride coating on the sodium ion battery positive electrode material NVPOF, and using microwave heating treatment, the problems of low electronic conductivity and Na+ diffusion rate of NVPOF are solved, significantly improving the electrochemical performance of the material.
Patent Information
- Application Number
- CN202310362528.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-04-07
AI Technical Summary
The existing sodium ion battery positive electrode material NVPOF has low electronic conductivity and low Na+ diffusion rate, resulting in limited electrochemical reactions and limiting the improvement of electrochemical performance.
The modified NVPOF precursor powder is synthesized by a one-step hydrothermal method by a transition metal doping method, and coated it with dopamine hydrochloride as a carbon source, and then heat treatment is performed by microwave heating to obtain a high specific capacity transition metal doped carbon-coated sodium vanadium fluorogenic sodium phosphate material.
Through doping and coating modification treatment, the electronic conductivity and Na+ diffusion rate of the material are significantly improved, the cyclic reversibility and rate performance of the material are improved, and higher specific capacity and more stable cyclic performance are obtained.
Smart Images

Figure CN116504964B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of electrode material preparation, and specifically relates to a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material. Background Art
[0002] As we all know, with the emergence of problems such as intensified environmental pollution and energy crisis, clean renewable energy and energy storage systems have developed rapidly. As one of the electrochemical energy storage systems, sodium-ion batteries have broad development prospects. However, a series of problems such as low energy density, low power density, and poor rate performance have become important reasons restricting their large-scale development. The positive electrode material is the key to improving the performance of sodium-ion batteries, so it is particularly important to develop sodium-ion battery positive electrode materials with excellent performance and low price.
[0003] NVPOF with NASICON structure is considered to be an ideal cathode material for low-cost sodium-ion batteries due to its high operating voltage platform, excellent structural stability and high specific capacity. + Problems such as low diffusion rate limit the electrochemical reaction, which in turn hinders the improvement of electrochemical performance.
[0004] In order to further improve the charge and discharge capacity and rate performance of NVPOF, it is usually modified (such as ion doping, carbon coating modification, etc.).
[0005] First, the traditional coating method is a one-step coating method, in which the carbon source is directly added during the material synthesis process. The direct addition of the carbon source will cause the NVPOF particles to not be fully mixed and contacted with the carbon source, resulting in uneven coating, which will aggravate the unevenness and irregularity of the particle size during the heat treatment process. It will have an adverse effect on the cyclic stability and rate performance of the material. Secondly, traditional heating methods such as solid-phase heating: heat transfer is achieved through conduction, convection, and radiation. This method will cause a large temperature difference between the inside and outside of the material, uneven heating, and an adverse effect on the nucleation and growth process of the grains, resulting in uneven particle size and increased particle agglomeration.
[0006] In view of this, this application is hereby filed. Summary of the invention
[0007] In order to solve one of the above technical defects, a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material is provided in an embodiment of the present application.
[0008] The technical solution of the present application provides a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material, comprising the following steps:
[0009] The modified NVPOF precursor powder was synthesized by a one-step hydrothermal method using transition metal doping;
[0010] The NVPOF precursor powder is coated with dopamine hydrochloride as a carbon source to form a polydopamine-coated NVPOF precursor powder;
[0011] The polydopamine-coated NVPOF precursor powder material is heat-treated by microwave heating, and naturally cooled to room temperature to obtain a high-purity and high-specific-capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material.
[0012] Preferably, the transition metal is any one of Fe, Nb, Co and Cu.
[0013] Preferably, the modified NVPOF precursor powder is synthesized by a one-step hydrothermal method by transition metal doping, which specifically includes the following steps:
[0014] Add V2O5, transition metal source and reducing agent into the reaction bottle and add deionized water to mix evenly;
[0015] Transfer the reaction bottle to a magnetic stirrer and heat and stir for 1-2 hours; then add NH4H2PO4 and continue heating and stirring for more than half an hour; finally add NaF to the dark blue solution, and after the preset reaction time, add ammonia water dropwise to the solution to adjust to the preset pH value;
[0016] The reaction bottle was sealed in a stainless steel outer bottle and subjected to a constant temperature hydrothermal reaction at 170°C for 12 hours;
[0017] Finally, the transition metal ion-doped NVPOF precursor powder is obtained by centrifugation, washing and drying.
[0018] Preferably, the transition metal source is any one of Fe2O3, Co2O3, Nb2O5, and Cu2O.
[0019] Preferably, the modified NVPOF precursor powder is synthesized by a one-step hydrothermal method by transition metal doping, specifically:
[0020] 0.004275 mol of V2O5, 0.00045 mol of transition metal source and 0.0135 mol of oxalic acid were added into a 50 ml polytetrafluoroethylene bottle and 30 ml of deionized water were added to mix evenly;
[0021] Transfer the reaction bottle to a magnetic stirrer and heat and stir for 1-2 hours at a reaction temperature of 40-80°C and a magnetic stirrer speed of 400 r / min, then add 0.009 mol of NH4H2PO4 and continue heating and stirring for more than half an hour until a dark blue solution is formed;
[0022] Add 0.0135 mol of NaF to the dark blue solution, and after the preset reaction time, add ammonia water dropwise to the solution to adjust the pH to 7;
[0023] The reaction bottle was sealed in a stainless steel outer bottle and subjected to a constant temperature hydrothermal reaction at 170° C. for 12 hours. Finally, the transition metal ion-doped NVPOF precursor powder was obtained by centrifugation, washing, and drying at 60° C.
[0024] Preferably, the NVPOF precursor powder is coated with dopamine hydrochloride as a carbon source to form a polydopamine-coated NVPOF precursor powder; comprising the following steps:
[0025] Dispersing a preset amount of NVPOF precursor powder into a Tris buffer solution, and uniformly dispersing it in the buffer solution by ultrasonic stirring;
[0026] Add a preset amount of dopamine hydrochloride according to the requirement of carbon layer thickness, and continue ultrasonic stirring for a preset time;
[0027] NVPOF@PDA was obtained by centrifugation, washing and drying.
[0028] Preferably, the polydopamine-coated NVPOF precursor powder material is heat-treated by microwave heating; specifically:
[0029] The dried polydopamine-coated NVPOF precursor powder was placed in a corundum crucible, and then placed in a microwave field. Under an Ar atmosphere, the gas flow rate was 50-100 sccm, the heating power was 800 W, the temperature was raised to 600°C, and the microwave irradiation reaction was performed for 120 minutes.
[0030] The technical solution of the present application also provides an application of a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material for preparing a positive electrode material.
[0031] Beneficial effects of this application:
[0032] 1. This application innovatively adopts the transition metal doping method, which adopts a step-by-step doping and coating modification method. First, the transition metal element doped precursor is synthesized by a one-step hydrothermal method, and then the precursor is evenly dispersed in a buffer solution, and then coated by adding PDA; finally, the material is heat-treated by microwave heating to obtain high-purity doped and coated sodium vanadium fluorophosphate. This modification method gives full play to the stable supporting role of transition metals as structural pillars. The coated carbon layer can inhibit grain growth and has a high conductivity.
[0033] 2. This method adopts a step-by-step doping and coating modification treatment method. Compared with the method of direct one-step coating during the synthesis process, the synthesis of the precursor first can effectively avoid the influence of the presence of PDA during the material synthesis process, thereby greatly improving the purity of NVPOF. At the same time, the step-by-step coating method can make each NVPOF particle surface evenly coated with a layer of PDA. Compared with the one-step coating method, the carbon layer is more uniform, and the inhibitory effect on excessive growth and agglomeration of grains during heat treatment is more obvious. And the coating time of PDA can be precisely controlled to meet the different requirements for the thickness of the carbon layer under different circumstances, so as to achieve the adjustability of the NVPOF particle size. This method prepares NVPOF nanoparticles with higher capacity, more uniform particle size and better dispersibility through the modification means of internal doping and external coating. At the same time, it solves the problem of Na + It has many advantages such as low diffusion rate, low electronic conductivity, etc. It has many advantages such as simple operation, environmental friendliness and high universality.
[0034] 3. In the process of NVPOF synthesis, any transition metal (Fe, Nb, Co, Cu, etc.) with a larger ionic radius is selected for doping to partially replace V in NVPOF. 4+ First, due to the doping ions and V 4+ There are differences in the ionic radius of the doped Figure 4 ) The comparison chart shows that the characteristic peak has shifted to the left, proving that the lattice of NVPOF has expanded after doping, thereby expanding the Na + migration channel, promoting Na + The presence of doping ions can act as a pillar during the charge and discharge process, buffering the deformation of the crystal structure and preventing the collapse of the lattice during the cycle, thereby inhibiting unfavorable phase changes. At the same time, due to the difference in electronegativity between the two ions, in order to maintain charge balance after doping, electron redistribution will occur, promoting more oxygen vacancies ( Figure 5 ) is produced. Therefore, metal ion doping can effectively solve the problems of low electronic conductivity and Na + The low diffusion rate and other problems further improve the cyclic reversibility of the material and reduce the + The strain caused by intercalation and deintercalation makes the material show extremely high reversible capacity and ultra-stable cycle performance.
[0035] 4. This application uses dopamine hydrochloride to coat the surface of each NVPOF particle with a layer of PDA evenly. During the heat treatment process, PDA will be carbonized into a layer of derived carbon evenly coated on the surface of the material. The coated carbon layer will inhibit the growth of grains to obtain small and uniform grains. The presence of the carbon layer can solve the problem of particle agglomeration caused by the heat treatment process and increase the conductivity of the material, greatly improving the rate performance of the material. At the same time, the uniformly coated carbon layer will shorten the Na + The migration path plays a great role in improving the capacity and cycle stability.
[0036] 5. The present application adopts microwave heating treatment to replace the traditional solid-phase heating method. First of all, the difference between microwave heating and solid-phase heating is that the heating method is different. Solid-phase heating is to achieve the purpose of heating by heat transfer in the form of conduction, convection, and radiation. This method will cause a large temperature difference between the inside and outside of the material, and the heating is uneven, which will have an adverse effect on the nucleation and growth process of the grains, thereby leading to the intensification of uneven particle size and particle agglomeration. Microwave heating is to generate heat for heating through the coupling effect of microwaves and the material itself. Compared with solid-phase heating, it has the advantages of instantaneous heating and overall heating, which not only avoids the problems caused by heating lag and uncontrollable cooling temperature in the solid-phase sintering process, but also can significantly improve the uniformity of heating, making the particle size of the material more uniform and more controllable. Secondly, due to the doping of metal ions, the lattice of the material will be distorted and defects will be generated inside the material. The defects generated will provide more paths for the transmission of microwaves, increase the number of microwave transmissions, make the microwave reaction more sufficient, and heat more evenly inside and outside, thereby improving the nucleation rate of the grains. The synergistic effect of doping and microwaves can increase the dispersion of particles, avoid uneven particle size, and greatly improve the performance of the material. At the same time, due to the instantaneous and holistic nature of microwave heating, the heat treatment operation of the material is more energy-saving and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0038] Figure 1 This is the scanning electron microscope image of the modified NVPOF;
[0039] Figure 2 This is the original NVPOF SEM image;
[0040] Figure 3 TEM image of NVPOF;
[0041] Figure 4The XRD spectra comparison diagram of modified NVPOF and original NVPOF;
[0042] Figure 5 This is the EPR comparison diagram of modified NVPOF and original NVPOF;
[0043] Figure 6 Comparison of the charge and discharge curves of the modified NVPOF and the original NVPOF.
[0044] Figure 7 It is the long cycle graph of NVPOF. DETAILED DESCRIPTION
[0045] In order to make the technical solutions and advantages in the embodiments of the present application more clearly understood, the exemplary embodiments of the present application are further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than an exhaustive list of all the embodiments. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict.
[0046] The embodiment of the present application provides a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material, comprising the following steps:
[0047] The modified NVPOF precursor powder was synthesized by a one-step hydrothermal method using transition metal doping;
[0048] The NVPOF precursor powder is coated with dopamine hydrochloride as a carbon source to form a polydopamine-coated NVPOF precursor powder;
[0049] The polydopamine-coated NVPOF precursor powder material is heat-treated by microwave heating, and naturally cooled to room temperature to obtain a high-purity and high-specific-capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material.
[0050] As a specific embodiment of the present application, a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material is provided, wherein the transition metal is any one of Fe, Nb, Co, and Cu.
[0051] As a specific embodiment of the present application, a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material is provided, wherein a modified NVPOF precursor powder is synthesized by a one-step hydrothermal method using transition metal doping, and specifically comprises the following steps:
[0052] Add V2O5, transition metal source and reducing agent into the reaction bottle and add deionized water to mix evenly;
[0053] Transfer the reaction bottle to a magnetic stirrer and heat and stir for 1-2 hours; then add NH4H2PO4 and continue heating and stirring for more than half an hour; finally add NaF to the dark blue solution, and after the preset reaction time, add ammonia water dropwise to the solution to adjust to the preset pH value;
[0054] The reaction bottle was sealed in a stainless steel outer bottle and subjected to a constant temperature hydrothermal reaction at 170°C for 12 hours;
[0055] Finally, the transition metal ion-doped NVPOF precursor powder is obtained by centrifugation, washing and drying.
[0056] As a specific embodiment of the present application, a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material is provided, wherein the transition metal source is any one of Fe2O3, Co2O3, Nb2O5, and Cu2O.
[0057] As a specific embodiment of the present application, a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material is provided, wherein the modified NVPOF precursor powder is synthesized by a one-step hydrothermal method using transition metal doping, specifically:
[0058] 0.004275 mol of V2O5, 0.00045 mol of transition metal source and 0.0135 mol of oxalic acid were added into a 50 ml polytetrafluoroethylene bottle and 30 ml of deionized water were added to mix evenly;
[0059] Transfer the reaction bottle to a magnetic stirrer and heat and stir for 1-2 hours at a reaction temperature of 40-80°C and a magnetic stirrer speed of 400 r / min, then add 0.009 mol of NH4H2PO4 and continue heating and stirring for more than half an hour until a dark blue solution is formed;
[0060] Add 0.0135 mol of NaF to the dark blue solution, and after the preset reaction time, add ammonia water dropwise to the solution to adjust the pH to 7;
[0061] The reaction bottle was sealed in a stainless steel outer bottle and subjected to a constant temperature hydrothermal reaction at 170° C. for 12 hours. Finally, the transition metal ion-doped NVPOF precursor powder was obtained by centrifugation, washing, and drying at 60° C.
[0062] As a specific embodiment of the present application, a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material is provided, wherein dopamine hydrochloride is used as a carbon source to coat an NVPOF precursor powder to form a polydopamine-coated NVPOF precursor powder; the method comprises the following steps:
[0063] Dispersing a preset amount of NVPOF precursor powder into a Tris buffer solution, and uniformly dispersing it in the buffer solution by ultrasonic stirring;
[0064] Add a preset amount of dopamine hydrochloride according to the requirement of carbon layer thickness, and continue ultrasonic stirring for a preset time;
[0065] NVPOF@PDA was obtained by centrifugation, washing and drying.
[0066] As a specific embodiment of the present application, a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material is provided, wherein a polydopamine-coated NVPOF precursor powder material is heat-treated by microwave heating; specifically:
[0067] The dried polydopamine-coated NVPOF precursor powder was placed in a corundum crucible, and then placed in a microwave field. Under an Ar atmosphere, the gas flow rate was 50-100 sccm, the heating power was 800 W, the temperature was raised to 600°C, and the microwave irradiation reaction was performed for 120 minutes.
[0068] As a specific embodiment of the present application, a method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material comprises the following specific steps:
[0069] S1: Preparation of NVPOF precursor
[0070] 0.004275mol of V2O5, 0.00045mol of Fe2O3 and 0.0135mol of oxalic acid were added to a 50ml polytetrafluoroethylene bottle and 30ml of deionized water was added for uniform mixing. The reaction bottle was transferred to a magnetic stirrer and heated and stirred for 1-2 hours (40-80°C, 400r / min), and then 0.009mol of NH4H2PO4 was added and continued to heat and stir for more than half an hour; finally, 0.0135mol of NaF was added to the dark blue solution, and ammonia water was added dropwise to the solution after a period of reaction to adjust the pH to 7±0.05. The reaction bottle was sealed in a stainless steel outer bottle and subjected to a constant temperature hydrothermal reaction at 170°C for 12 hours. Finally, the transition metal ion-doped precursor powder (NVPOF) was obtained by centrifugation, washing and drying (60°C).
[0071] S2: Preparation of NVPOF@PDA
[0072] A certain amount of NVPOF precursor powder was dispersed in Tris buffer solution, and ultrasonic stirring was performed for more than 30 minutes to make it uniformly dispersed in the buffer solution. Then, an appropriate amount of dopamine hydrochloride was added according to the requirements of the carbon layer thickness, and ultrasonic stirring was continued. The stirring time can also be adjusted according to the coating requirements. Then, NVPOF@PDA was obtained by centrifugation, washing, and drying.
[0073] S3: Put the dried NVPOF@PDA into a corundum crucible, and then put it into a microwave field. Under Ar atmosphere (gas flow rate 50-100sccm), heat it to 600°C with a heating power of 800W, microwave irradiate and react for 120 minutes. After naturally cooling to room temperature, high-purity NVPOF@PDA electrode material can be obtained.
[0074] As a specific embodiment of the present application, an application of a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material is also provided for preparing a positive electrode material.
[0075] like Figure 1 , Figure 2 The following are the scanning electron microscope images of the modified NVPOF and the original NVPOF. The SEM images show that the particles after doping and coating are cubes with a particle size of 400-500nm. Compared with the original NVPOF, the particle size is smaller and the distribution is more uniform.
[0076] Figure 3 This is the TEM image of NVPOF; through TEM, it can be seen that the particles are evenly coated with a carbon layer.
[0077] Figure 4 The XRD spectra of modified NVPOF and original NVPOF are shown in Figure 2. Figure 3 It can be seen that compared with the original NVPF, the characteristic peaks of the modified material shifted to the left as a whole, proving that lattice expansion occurred after modification and the diffusion channel of Na+ became larger.
[0078] Figure 5 This is the EPR comparison diagram of the modified NVPOF and the original NVPOF, which proves that more oxygen vacancies are generated after doping to balance the charge.
[0079] Figure 6 The figure shows the charge and discharge curve of NVPOF, which proves that the modified material has a higher voltage platform, smaller polarization, and a higher energy density.
[0080] Figure 7 The figure shows the long cycle diagram of NVPOF; the material can still maintain a capacity of 125 mAh / g after 500 cycles and has an extremely high capacity retention rate.
[0081] In summary, this method adopts a step-by-step doping and coating modification treatment method. First, a transition metal element-doped precursor is synthesized by a one-step hydrothermal method, and then the precursor is evenly dispersed in a buffer solution, and then coated by adding PDA. Compared with the method of direct one-step coating during the synthesis process, synthesizing the precursor first can well avoid the influence of the presence of PDA during the material synthesis process, thereby greatly improving the purity of NVPOF. At the same time, the step-by-step coating method can make each NVPOF particle surface evenly coated with a layer of PDA. Compared with the one-step coating method, the carbon layer is more uniform, and the inhibitory effect on excessive growth and agglomeration of grains during heat treatment is more obvious. And the coating time of PDA can be precisely controlled to meet the different requirements for the thickness of the carbon layer under different circumstances, so as to achieve the adjustability of the NVPOF particle size. This method prepares NVPOF nanoparticles with higher capacity, more uniform particle size and better dispersibility through the modification means of internal doping and external coating. At the same time, it solves the problem of Na + It has many advantages such as low diffusion rate, low electronic conductivity, etc. It has many advantages such as simple operation, environmental friendliness and high universality.
[0082] It is worth noting that the present application makes the proposed step-by-step metal ion doping, dopamine hydrochloride coating and internal and external modification strategy and the synthesis method of sodium vanadium fluorophosphate by heat treatment through microwave heating protected by patents. In this method, the types of vanadium salts and reducing agents are adjustable, and similar vanadium salts and reducing agents using this method are within the scope of protection.
[0083] It is worth noting that the innovative details of the technical steps S1-S3 of this application, including but not limited to the above parameters, such as material proportions, heating temperature, heating power and insulation time, air flow rate, etc., are all protected by patents.
[0084] Although the preferred embodiments of the present application have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of the present application.
[0085] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
Claims
1. A method for preparing a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material, characterized in that: The steps include: The modified NVPOF precursor powder was synthesized by a one-step hydrothermal method using transition metal doping; The NVPOF precursor powder is coated with dopamine hydrochloride as a carbon source to form a polydopamine-coated NVPOF precursor powder; specifically, a preset amount of NVPOF precursor powder is dispersed in a Tris buffer solution, and ultrasonic stirring is performed to uniformly disperse the powder in the buffer solution; a preset amount of dopamine hydrochloride is added according to the requirements for the thickness of the carbon layer, and ultrasonic stirring is continued for a preset time; centrifugation, washing, and drying are performed to obtain NVPOF@PDA; The polydopamine-coated NVPOF precursor powder material is heat-treated by microwave heating, and naturally cooled to room temperature to obtain a high-purity and high-specific-capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material.
2. The preparation method according to claim 1, characterized in that The transition metal is any one of Fe, Nb, Co and Cu.
3. The preparation method according to claim 1, characterized in that: The modified NVPOF precursor powder is synthesized by a one-step hydrothermal method by transition metal doping, which specifically includes the following steps: Add V2O5, transition metal source and reducing agent into the reaction bottle and add deionized water to mix evenly; Transfer the reaction bottle to a magnetic stirrer and heat and stir for 1-2 hours; then add NH4H2PO4 and continue heating and stirring for more than half an hour; finally add NaF to the dark blue solution, and after the preset reaction time, add ammonia water dropwise to the solution to adjust to the preset pH value; The reaction bottle was sealed in a stainless steel outer bottle and subjected to a constant temperature hydrothermal reaction at 170°C for 12 hours; Finally, the transition metal ion-doped NVPOF precursor powder is obtained by centrifugation, washing and drying.
4. The preparation method according to claim 3, characterized in that: The transition metal source is any one of Fe2O3, Co2O3, Nb2O5, and Cu2O.
5. The preparation method according to claim 3, characterized in that: The modified NVPOF precursor powder was synthesized by a one-step hydrothermal method using transition metal doping, specifically: 0.004275 mol of V2O5, 0.00045 mol of transition metal source and 0.0135 mol of oxalic acid were added into a 50 ml polytetrafluoroethylene bottle and 30 ml of deionized water were added to mix evenly; Transfer the reaction bottle to a magnetic stirrer and heat and stir for 1-2 hours at a reaction temperature of 40-80°C and a magnetic stirrer speed of 400 r / min, then add 0.009 mol of NH4H2PO4 and continue heating and stirring for more than half an hour until a dark blue solution is formed; Add 0.0135 mol of NaF to the dark blue solution. After the preset reaction time, add ammonia water dropwise to the solution to adjust the pH to 7. The reaction bottle was sealed in a stainless steel outer bottle, and subjected to a constant temperature hydrothermal reaction at 170° C. for 12 hours; finally, the transition metal ion-doped NVPOF precursor powder was obtained by centrifugation, washing, and drying at 60° C.
6. The preparation method according to claim 1, characterized in that: The polydopamine-coated NVPOF precursor powder material is heat-treated by microwave heating; specifically: The dried polydopamine-coated NVPOF precursor powder was placed in a corundum crucible, and then placed in a microwave field. Under an Ar atmosphere, the gas flow rate was 50-100 sccm, the heating power was 800 W, the temperature was raised to 600°C, and the microwave irradiation reaction was performed for 120 minutes.
7. Application of a high specific capacity transition metal-doped carbon-coated sodium vanadium fluorophosphate material, characterized in that: The sodium vanadium fluorophosphate material is prepared by the method described in any one of claims 1 to 6 and is used to prepare a positive electrode material.
Citation Information
Patent Citations
Composite cathode material of sodium-ion battery and preparation method of composite cathode material
CN105655565A
Positive electrode material for transition metal-doped sodium ion battery and preparation and application thereof
CN109755565A
Different-valence-state manganese-doped Na3V2(PO4)2F3 carbon-coated cubic crystal material as well as preparation method and application thereof
CN114084882A
Method for preparing sodium vanadium phosphate positive electrode material by microwave method
CN115178209A